Egg quality characteristics of South African Potchefstroom Koekoek and commercial Lohmann brown layer chickens: A comparative study - Victoria Rankotsane Hlokoe; Thobela Louis Tyasi; Vusi Gordon Mbazima (PLoS ONE, 2026)
Egg quality is an important feature in egg production and is affected by many factors, including the genetic makeup of the bird. However, the influence of the chicken genotype on egg quality traits is limited and inconclusive. Therefore, this study aimed to highlight the influence of genotype on the external and internal egg quality traits of the Potchefstroom Koekoek and Lohmann Brown layers. A total of 600 eggs (300 eggs per genotype) was used, and a cross-sectional experimental design was used. The findings displayed that all external egg quality traits were significantly (P < 0.05) affected by the genotype, except for the unit shell surface weight (P ≥ 0.05). The outcomes also displayed that the genotype significantly (P < 0.05) affected all internal egg quality traits. The most affected traits favored the Lohmann Brown over the Potchefstroom Koekoek chickens. In conclusion, the outcomes showed significant differences in the external egg quality traits such as the egg length, shell weight, eggshell index, egg width and shell ratio, and the significant differences in the internal egg quality traits such as yolk/ albumen, yolk weight, albumen weight, albumen ratio and yolk ratio between the Potchefstroom Koekoek and Lohmann Brown chickens.